Anterior abdominal wall defects: Demographic and clinical profile and outcome at a tertiary care hospital - Kumar, Parveen; Manchanda, Vivek; Sengar, Mamta (Journal of Neonatal Surgery, 2021)
Background: The anterior abdominal defects, especially gastroschisis and omphalocele have high mortality rates in developing countries. Time to intervene has been hypothesized to be associated with morbidity and mortality. The aim was to determine factors affecting mortality in neonates with anterior abdominal wall defects. Methods: This retrospective descriptive study was done at a tertiary pediatric care center. The medical records of patients with a diagnosis of anterior abdominal defects (omphalocele/gastroschisis/umbilical cord hernia) admitted at our center from Jan 2015 to Dec 2019 were retrieved. The demographic and clinical data were studied including age, sex, religion, gestational age, associated anomalies, electrolytes at admission, septic profile, operative details, length of hospital stay, and mortality. The statistical data was fed on a Microsoft Excel worksheet and analysis was done. Results: Thirty-nine (39) neonates were included in the study. M:F ratio was 2:1, with 61.5% belonging to the Hindu religion. The majority had term gestation (87.2%). Birth weight ranged from 1.5 to 4 kg (mean 2.47 ±0.5 kg). Eighteen (18) neonates had gastroschisis, 15 omphalocele major and 6 omphalocele minor, with a median age of presentation at 1 day of life. Time to intervention ranged from 0 to 5 days (interquartile range 1-1.25 days) after admission. Primary closure could be achieved in the majority (66.7%), while ventral hernia was created in 17.9% and the silo was needed in the rest. The mean postoperative length of stay was 9.31 days (±9.85 days) with a survival rate of 38.5%. The mortality rate in gastroschisis and omphaloceles were 61.1% and 38.1% respectively. The significant factors for survival were birth weight, and primary abdominal wall closure. Conclusions: The present study brings out a different clinical profile of anterior abdominal wall defect patients. We recommend early surgery soon after stabilization and primary abdominal wall repair whenever abdominal pressures permit.